1999
DOI: 10.1038/sj.bjc.6690790
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of various invasion assays testing colon carcinoma cell lines

Abstract: Summary Various colon carcinoma cell lines were tested in different invasion assays, i.e. invasion into Matrigel, into confluent fibroblast layers and into chicken heart tissue. Furthermore, invasive capacity and metastatic potential were determined in nude mice. The colon carcinoma cells used were the human cell lines Caco-2, SW-480, SW-620 and HT-29, and the murine lines . None of the human colon carcinoma cells migrated through porous membranes coated with Matrigel; of the murine lines, only Colon-26 did. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 19 publications
4
31
0
Order By: Relevance
“…The SD cell line was not invasive in vitro, but after subcutaneous injection and after inoculation in the bladder wall, SD cells developed muscle-invasive tumors. Similar discrepancies between the embryonic chicken heart invasion assay and in vivo invasiveness were reported earlier in a study on colorectal carcinoma cell lines [11,12]. Our results support the view that the microenvironment may regulate invasive behavior of bladder carcinoma cells in vivo, for instance by influencing the expression of E-cadherin, as suggested by Mareel et al [21] or by induction of synthesis of extracellular matrix degrading proteins [33].…”
Section: Discussionsupporting
confidence: 90%
“…The SD cell line was not invasive in vitro, but after subcutaneous injection and after inoculation in the bladder wall, SD cells developed muscle-invasive tumors. Similar discrepancies between the embryonic chicken heart invasion assay and in vivo invasiveness were reported earlier in a study on colorectal carcinoma cell lines [11,12]. Our results support the view that the microenvironment may regulate invasive behavior of bladder carcinoma cells in vivo, for instance by influencing the expression of E-cadherin, as suggested by Mareel et al [21] or by induction of synthesis of extracellular matrix degrading proteins [33].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we found that Crispr-mediated SRC1/2/3 or Dock4/9 knockout inhibited YAP5SA/JunD-dependent migration in HT29 cells (Figure 5H–J), highlighting the functional importance of these proteins in YAP/Tead-AP1 cooperation. Next, we demonstrated that the combined inhibition of Tead and AP1 activity in the highly invasive HCT116 colon cancer cells (de Both et al, 1999) led to effective inhibition of cell migration and invasion, measured by cell scratch and matrigel invasion assays (Figure 5K–M). Moreover, we analyzed the expression of JunD and Tead4 in sixty two human lung adenocarcinomas and their matched lymph node metastases, and found that JunD and Tead4 proteins were expressed significantly higher in the lymph node metastases than in the matched primary cancers (Figure 5N–Q), suggesting that the potential involvement of Tead-AP1 cooperation in promoting tumor invasion and metastasis.…”
Section: Resultsmentioning
confidence: 92%
“…To test this hypothesis, we ectopically expressed YAP5SA and JunD in the HT29 cells, a relatively less invasive colon cancer cell line (de Both et al, 1999), and found that YAP5SA and JunD co-expression significantly promoted migration of HT29 cells, measured by transwell migration assay (Figure 5F). In addition, we showed that YAP5SA or TAZ4SA (an active form of TAZ) induced migration was partially inhibited by DN-JunD (Figure 5G).…”
Section: Resultsmentioning
confidence: 99%
“…Invasion and migration assays based on the already established co-culture model will clarify this issue in future experiments. Although Caco-2 cells appear to be noninvasive in nude mice (65), secretory products of cells in the vicinity may interact at the surface of the cancer cells and by this increase their invasive potential. For instance, migration of Caco-2 cells in wounded cell layers was stimulated 2-3-fold by exogenous u-PA, an effect dependent on binding to u-PAR (57).…”
Section: Figmentioning
confidence: 99%
“…In vitro, trypsin cleaves the propeptide of human meprin following an Arg residue (Arg 65 in human meprin-␣ and Arg 61 in human meprin-␤) (18), and this is most probably the physiologic mechanism of promeprin activation in the intestinal lumen. However, possible other meprin-activating proteases must exist in vivo, especially in meprin-expressing tissues or cells, where trypsin is absent.…”
mentioning
confidence: 99%